First and second sound in a dilute Bose gas across the BKT transition. (1st July 2022) - Singh, Vijay Pal; Mathey, Ludwig
Abstract: We study the propagation of the two sound modes in two-dimensional Bose gases across the Berezinksii–Kosterlitz–Thouless transition using classical-field dynamics, which is motivated by recent measurements of Christodoulou et al (2021 Nature 594 191). Based on the dynamic structure factor (DSF), we identify the two sound modes as the Bogoliubov (B) and the non-Bogoliubov (NB) sound mode below the transition, and as the diffusive and the normal sound mode above the transition. The NB sound mode velocity is higher than the B sound mode velocity, which we refer to as the weak-coupling regime of the sound modes. We excite the sound modes by driving the system as in the experiment and by perturbing the density with a step-pulse perturbation, as a secondary comparison. The driven response depends on the driving strength and results in higher velocities for the B sound mode at high temperatures near the transition, compared to the sound results of the DSF and step-pulse excitation. We show that the higher mode velocity has a weak temperature dependence across the transition, which is consistent with the experimental observation.